Frankie and friend - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Frankie and male friend. Frankie (left) was H.I.M. Emperor XXVI and is wearing a polka dot sweater. He is beside his taller friend who is wearing a light colored shirt.